Effectiveness of Ganz Repositioning Maneuver (GRM) Compared with Epley’s Repositioning Maneuver (ERM) in the Management of Posterior Canal-Benign Paroxysmal Positional Vertigo (PC-BPPV): Implications for quality of life, daily functioning and psychosocial Well-being - Nukhbat Ullah Awan; Ayesha Aslam; Rabia Zulfiqar; Dilawaiz; Syeda Hamda; Azmir Ali Khan; Muhammad Azeem Malik; Anurag Jha (Kurdish Studies, 2024)
Background: Vertigo, with a prevalence of 5–10 %, is a common complaint of patients presenting to otolaryngology and neurology departments. Benign paroxysmal positional vertigo (BPPV), coined by Barany in 1921, is the most common cause of true vertigo. The condition is described as brief episodes of intense vertigo, provoked by changing position of head/neck, and typically accompanied by nystagmus with the superior pole of the eyes beating toward the affected ear. Causative factor is the displacement of Otoconia from the utricle to these semicircular canal. BPPV may be associated with a reduced quality of life, falls and depression. Different Maneuvers are reported in literature for treatment of BPPV. Treatment can be performed in clinic with a good outcome, making it the most rewarding vestibular condition to manage. Objective: This study was designed to compare between the effectiveness of Gans Repositioning Maneuver and Epley’s Repositioning Maneuver in improving postural stability in patients of Posterior Canal-BPPV. Method: A total of 140 patients were enrolled in this study where 70 were recruited into Group-A who were treated with Gans Repositioning Maneuver and the 70 in Group-B ,treated with Epley’s Maneuver , for Posterior Canal-BPPV. All the patients were examined and treated at ENT department KEMU/Mayo Hospital Lahore between January 2021 to October 2021. Patients who were clinically positive on Dix-Hallpike test, having unilateral canal involvement and aged between 18 years to 65 years were included and those with bilateral canal involvement, past ear surgery and severe neck or back restrictions for movement were excluded from our study. Every patient received one treatment maneuver per appointment once a week. Maneuver was repeated each week until resolution of symptoms of vertigo and nystagmus. No post-maneuver restrictions were taken into account for any patient. Participants provided a subjective report of intensity of their vertigo using a visual analog scale (VAS) from 0 to 10. A rating of 0 indicated no subjective vertigo and a rating of 10 indicated the greatest magnitude of vertigo. After every session, each participant was assessed with this scale to quantify the level of improvement. Once the patient became vertigo free, follow up for the incidence of recurrence at 1, 3 and 6 months’ period of time from final successful treatment was done. Success was defined by the absence of nystagmus and positional vertigo during Dix-Hallpike test. Result: Out of total 140 patients , 91 (65%) patients were female and 49 (35%) were of male gender. Posterior canal BPPV was found to be more common in patients above 40 years of age, with 89 (63.6%) patients were over 40 years of age and 51 (36.4%) were below 40 years of age. Nausea was reported to be among 27.1 % (19 patients) in group-A and it was 38.5% (27 patients) in Group-B. Similarly; Vertigo was reported to be among 52.8 % (74 patients) in group-A and it was 47.14% (66 patients) in Group-B. The recurrence rate for group-A turned out to be 8.5% (6 patients) and for Group-B it came 20% (14 patients) at 6 month follow up from last successful maneuver. Group-A patients were successfully treated with success rate of 91.4% (64 patients), while the success rate of Group-B patients came out to be 80% (56 patients). Conclusion: We concluded with the results of our study that Gans repositioning maneuver (GRM) is a safe and more effective particle repositioning maneuver for the treatment of vertigo in patients with posterior SCC-BPPV than Epley’s Repositioning Maneuver (ERM), having less recurrences and less complications.